Stop and account process - Cojocaru, Elena (Eximia, 2023)
Over time, we notice that the measure of identification of persons has undergone small changes, and the refusal of identification has become a problem among police officers performing their duties. Thus, the laws were created to ensure public order and the safety of citizens, and then to sanction violators. In the theme, we took into account what various authors have published in the books written by them, regarding the identification of people and all the activities that a policeman has the obligation to perform, as well as the laws by which the French police carry out their activity. The purpose of stop and account a person is to procure a set of rules for establishing a person's identity and carrying out the tasks regarding the preparation and approval of the documents related to this procedure. Romanian and foreign citizens have the obligation to legitimize themselves on the territory of Romania either with an identity document, or verbally if they do not have any document on them, whenever they are asked to do so by the officers and agents of the Romanian Police, as well as on the territory of France.